Clinical Features and Efficacy Analysis of Redundant Nerve Roots - Xu, Jianzhong; Hu, Yong (Frontiers in Surgery, 2021)
Introduction：Redundant nerve roots (RNRs) are common finding in lumbar spinal stenosis patients. Up to now, many relevant studies were carried out on the mechanism, pathogenic factors and clinical features of redundant nerve roots. However, there are few studies on the surgical methods. In this study, posterior lumbar interbody fusion and internal fixations were used in 30 patients with RNRs in our hospital. Moreover, we also proposed new ideas about different types and subtypes of RNRs using patterns and their corresponding MRI images. Methods：Thirty patients with lumbar spinal stenosis and RNRs were enrolled in this study and underwent surgery between January 2009 and December 2014. Redundant nerve roots are identified as elongated, tortuous, or serpiginous nerve roots present in the subarachnoid space on sagittal T2-weighted magnetic resonance imaging (MRI) studies. Patients were treated with posterior decompression, intervertebral disc resection, and instrumented interbody fusion. The age, sex, disease course, operative time, intraoperative blood loss, operative segments were recorded. Outcome measures recorded to identify symptom improvement included preoperative and postoperative visual analogue scale (VAS), preoperative and postoperative Oswestry disability index (ODI) and preoperative and postoperative Japanese Orthopaedic Association (JOA) scores. Results：VAS back pain, VAS leg pain VAS, ODI and JOA with standard deviations were 6.4±0.9, 7.1±0.8, 43.0±2.2 and 10.3±2.6, respectively． At 3 months postoperatively, VAS back pain, VAS leg pain VAS, ODI and JOA with standard deviations were 1.4±0.5, 1.6±0.6, 13.0±1.6 and 25.0±1.8, respectively. Nerve redundancy resolved in all cases on postoperative MRI. Conclusion：Posterior lumbar laminectomy and instrumented interbody fusion relieves low back and leg pain in patients with lumbar spinal stenosis and RNRs and can alleviate the tortuous appearance of the cauda equina in the decompressed segment.